Improvisation as a Curricular Metaphor: Imagining Education for a Rural Creative Class - Michael Corbett (Journal of Research in Rural Education, 2013)
Rural communities contain a largely unacknowledged innovative capacity founded on improvisational traditions. These traditions may be rooted in work practices in agriculture and other rurally-based productive activities but today they have expanded into other lifeworld locations, particularly virtual spaces that accelerate time-space compression. I make the case here that in the networked world of high modernity or postmodernity, both the nature of rurality and the potential of rural education need to be theorized differently. I begin with a critique of Richard Florida's metrocentric idea of the creative class, then move to reconceptualizing rurality as a real and imagined space, and conclude by analyzing a fi lm and video project in an Atlantic Canadian school that used improvisation in literacy curriculum work. I argue that improvisation is a potentially productive metaphor for curriculum, one which draws on rural traditions and local funds of knowledge while at the same time incorporating a productive, forward-looking engagement with new technologies.